Electrochemical Characterization of Bis‐Cobalt Hexaphyrin: A Selective Electrocatalyst for the Two‐Electron Reduction of Oxygen in Acid Media. Issue 5 (3rd March 2021) - Ye, Lina; Fang, Yuanyuan; Ou, Zhongping; Feng, Ru; Chen, Minyuan; Guo, Rui; Kadish, Karl M.
Abstract: A bis‐cobalt(II) hexaphyrin was synthesized and characterized as to its electrochemical and spectroelectrochemical properties in nonaqueous media. The examined compound is represented as HexaPyCo2 where HexaPy represents an expanded macrocycle containing six pyrroles and six meso ‐2, 6‐difluorophenyl substituents. Three or four reductions can be observed for the bis‐cobalt hexaphyrin depending upon the solvent. The first two reductions are reversible and well separated in PhCN ( E 1/2 =−0.50 and −0.90 V) or CH2 Cl2 ( E 1/2 =−0.52 and −0.87 V) containing 0.1 M TBAP. This contrasts with what is observed in pyridine where the first two one‐electron additions are overlapped in potential and occur at an apparent E 1/2 =−0.73 V vs SCE. The third and fourth reductions of the bis‐cobalt(II) hexaphyrin are irreversible and coupled to chemical reactions in PhCN or CH2 Cl2 but well‐defined one‐electron transfers are seen in pyridine where the 250 mV difference between reversible E 1/2 values (−1.28 and −1.53 V) matches almost perfectly with a 240 mV separation in potentials between the third and fourth reductions of a related bis‐Cu(II) hexaphyrin under the same solution conditions. The oxygen reduction reaction (ORR) was also investigated using HexaPyCo2 as a catalyst in 1.0 M HClO4 . The results of rotating‐disk and rotating‐ring‐disk voltammetry show that the bis‐cobalt hexaphyrin is a selective catalyst for the 2‐electron ORR and gives 95 % H2 O2 as the product in acid media. Abstract : Spinning wheel : A bis‐cobalt(II) hexaphyrin was electrochemically characterized in nonaqueous media and the electrocatalytic property of the compound for the oxygen reduction reaction was examined by rotating‐disk and rotating‐ring‐disk electrode techniques in acid solution.